Dual Encryption in a Shape Memory Hydrogel with Rewritable Fluorescent Information. Issue 8 (30th January 2023) - Tang, Junyi; Xing, Tianyu; Feng, Jiachun
Abstract: With the increasing emphasis on information security, reliable information encryption materials have been urgently desired. Herein, a hydrogel‐based dual encryption platform with self‐erasure function is developed, which exhibits both high‐security level and possibility of reuse. Dual encryption of the hydrogel‐based platform is realized by elegantly combining 2D fluorescent information pre‐written/printed via competitive coordination with pH‐induced shape deformation of the PSSA/PDEAEMA‐APA/Eu 3+ hydrogel. On‐demand decryption of the concealed information is realized by immersing the platform in solution of specific pH and exposed to 254 nm irradiation, which fully utilizes simultaneous shape recovery and fluorescence quenching of the hydrogel. With prolong of the immersion time, the carried information self‐erases permanently, which effectively prevents leakage of information to non‐recipient and further ensures information security. Thanks to the reversible pH‐responsive behaviors and repeatable self‐erasure ability, the hydrogel‐based dual encryption platform could recover to a 2D blank plane after decryption and self‐erasure, which is of great potential in high‐security information encryption. Abstract : A hydrogel‐based dual encryption platform with rewritable information is developed. The dual encryption is realized by combining fluorescent information and subsequent 2D‐to‐3D conversion. By utilizing simultaneous fluorescence quenching and shape recovery process of the pH‐responsive PSSA/PDEAEMA‐APA/Eu 3+ hydrogel, concealed information is on‐demand decrypted. Since the carried information realize self‐erasure with prolong of decryption process, the platform can be reused.